Recent Application of Enzymes and Microbes in Bioremediation - Eneji, Emmanuel Afen; Stephen, Ezeonu Chukwuma; Ikwebe, Joseph (African Journal of Biochemistry and Molecular Biology Research, 2024)
Chemicals used in industry and military, along with poor waste management, cause soil, water, and air pollution. Pollutants pose health risks due to their resistance to degradation processes. Conventional methods are costly and generate secondary pollution. Bioremediation offers eco-friendly alternatives using enzymes and nanotechnology for efficient pollutant removal either in situ or ex sit. Microorganisms play a crucial role in bioremediation by converting toxic elements into less harmful compounds through processes like mineralization. They can survive in diverse environments and utilize various substrates, making them efficient in removing pollutants. Microbes utilize mechanisms like immobilization and mobilization to remove pollutants from the environment, with different types of bacteria specializing in degrading specific pollutants. Enzyme engineering involves manipulating biomolecules and processes for biotechnological applications. Two main strategies are rational design, requiring prior knowledge, and directed evolution, mimicking natural selection in a controlled manner. Rational design combines microorganisms or enzymes for specific reactions, while directed evolution creates gene variants through random mutagenesis for desired characteristics. Both methods aim to improve enzymes for bioremediation applications.